2007
DOI: 10.1093/jnci/djm249
|View full text |Cite
|
Sign up to set email alerts
|

Interpreting Trends in Prostate Cancer Incidence and Mortality in the Five Nordic Countries

Abstract: Trends in incidence and mortality rates of prostate cancer were analyzed using data from the national cancer registries of Denmark, Finland, Iceland, Norway, and Sweden. Joinpoint regression models were used to quantify temporal trends for the period from 1980 to 2004. Incidence rates were increasing and similar in the Nordic countries during the 1980s. Around 1990, a more rapid incidence increase began in all Nordic countries except Denmark, where an increase was seen 5 years later. In 2001, incidence rates i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
127
0
5

Year Published

2009
2009
2016
2016

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 165 publications
(138 citation statements)
references
References 38 publications
6
127
0
5
Order By: Relevance
“…Therefore, the incidence must be interpreted in the context of prostate cancer-related diagnostic activity. This is exemplified by the Danish experience during the past three decades, where both the level of diagnostic activity and the prostate cancer incidence have been lower than in the other Nordic countries [108,109]. Before the introduction of PSA testing in the late 1980s, trans-urethral resections of the prostate (TURP), widely applied as a treatment for benign prostate hyperplasia, were responsible for a large number of incidental findings of prostate cancer.…”
Section: Prostate Cancermentioning
confidence: 99%
“…Therefore, the incidence must be interpreted in the context of prostate cancer-related diagnostic activity. This is exemplified by the Danish experience during the past three decades, where both the level of diagnostic activity and the prostate cancer incidence have been lower than in the other Nordic countries [108,109]. Before the introduction of PSA testing in the late 1980s, trans-urethral resections of the prostate (TURP), widely applied as a treatment for benign prostate hyperplasia, were responsible for a large number of incidental findings of prostate cancer.…”
Section: Prostate Cancermentioning
confidence: 99%
“…From population-based registries, data on the baseline characteristics of patients included might be used to analyze temporal trends in PCa presentation and risk [48][49][50][51]. In the five Nordic countries, an analysis of incidence and mortality data revealed a rapid increase in PCa incidence during the early 1990s coinciding with the introduction of PSA testing, while mortality rates stabilized or declined in countries where PSA testing and curative treatment have been commonly practiced since the late 1980s [52]. In addition, tumor registries can provide incidence and mortality data on patients with rare histologic subtypes that are not included in RCTs or institutional cohorts [53].…”
Section: 4mentioning
confidence: 99%
“…[21] The researchers have found that in the United States of America, Canada, France, Germany, and Spain, where PSA tests were routinely used, PCa-related mortality decreased, while in countries where PSA tests were not routinely performed including Belgium, Denmark, Greece, Ireland, and Bulgaria, PCa-specific mortality rates increased steadily. [22][23][24] Besides, in the Austrian state of Tyrol where PSA tests were routinely used PCa-related mortality rates decreased 54%, while in other regions of Austria where PSA tests were not routinely performed, mortality rates decreased only at a rate of 29 percent. [25] Based on these data, PSA screening apparently decreases PCa-related mortality rates.…”
mentioning
confidence: 99%